Handling of area impact of land exploitation in the Kendeng Mountain, Pati District, Central Java - Rozy, Fathur; Aliyudin, Mohamad; Mirna, Sufi; Ayu, Risa (Calamity: A Journal of Disaster Technology and Engineering, 2023)
The Kendeng Mountains are the largest limestone producer on the island of Java, so mining or over-exploitation is often carried out in several locations. Pati Regency is a city affected by the exploitation of the Kendeng Mountains, in addition to Rembang Regency. The northern Kendeng area, which is in southern Pati, has experienced more than 60% deforestation. The impacts of this exploitation are floods, droughts, and landslides in the South Pati region. Since 2019 the southern Pati region has experienced quite large flash floods approximately 5 times. To deal with the impact of exploitation this research uses analysis and synthesis methods. The clearing of forest land use as an agricultural and mining area in this location continued to occur from 1996 to 2016, and the rainfall that experienced the La Nina phenomenon in 2020/2021 caused flooding in the Tambakromo, Kayen, Sukolilo, and Winong areas. and drought in 30 villages, in the Pati region, Central Java. To maintain the impact of exploitation, reforestation must be carried out, construction of drainage canals, and construction of springs